(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
Sorghum Sorghum bicolor (L.) Moench is used as a grain, fodder, technical and food crop. The aim of our research was to determine the effect of different forms and doses of fertilizers on the yield of new hybrids of grain sorghum in the conditions of the Eastern Forest-Steppe of Ukraine. A two-factor field experiment was established using the split-plot method in three replications on the experimental field of the State Biotechnological University, which is located in the Eastern Forest-Steppe of Ukraine. For the completeness of the research and the evaluation of the obtained results, generalizing, field and statistical methods were used. The study of the effect of different systems of application of organic and mineral fertilizers in different parts of the world indicates that their use in agroecosystems, South Sudan, India, Ethiopia, African countries and other countries contributes to an increase in the yield of sorghum grain, improvement of the quality of the grown crop, increase in the profitability of grain and various types of feed from sorghum crops. Domestic researchers offer various fertilization systems for the formation of stable grain yields and improving its quality in the soil and climatic zones of Ukraine. According to the average three-year (2021, 2023–2024) research results, it was established that in the conditions of the Eastern Forest-Steppe of Ukraine it is advisable to grow the medium-early hybrid Aggyl and the early-ripening hybrid Brigga of French selection, which in this research area have a vegetation period of 124 and 119 days, respectively. With the option of applying Renovation Fuerza at a dose of 100 kg/ha, a yield of 7.75 and 7.41 t/ha of grain was obtained, respectively. Both hybrids with this option of fertilizer application under different weather conditions form a consistently high yield. The increase in grain yield of the Aggyl hybrid compared to the absolute and zonal controls was 2.04 and 2.49 t/ha and 1.18 and 1.63 t/ha, respectively, or 26.9 and 31.9 and 9.2 and 13.4 %. The superiority of the medium-early grain sorghum hybrid Aggyl over the early-ripening Brigga hybrid has been mathematically proven in all years of research. In the conditions of the Eastern Forest-Steppe of Ukraine, sowing of these hybrids and application of Renovation Fuerza fertilizer at a dose of 100 kg/ha should be combined. The share of different stem systems of grain sorghum hybrids in the total biological grain yield varies depending on the application of different forms and doses of fertilizers. Weather conditions of the growing season have a significant impact. The maximum percentage of main stems was formed in the Aggyl and Brigga hybrids under the option of applying Renovation Fuerza at a dose of 100 kg/ha.